Rehabilitation of motor function after stroke: A bibliometric analysis of global research from 2004 to 2022 - Hu, Jinjing; Zou, Jihua; Wan, Yantong; Yao, Qiuru; Dong, Peng; Li, Gege; Wu, Xuan; Zhang, Lijie; Liang, Donghui; Zeng, Qing; Huang, Guozhi (Frontiers in Aging Neuroscience, 2022)
Background and aims: The number of stroke deaths showed an increasing trend worldwide. Most surviving stroke patients have various somatic dysfunctions. Rehabilitation of motor function after stroke can improve their quality of life, which has long been the main method of functional recovery. Therefore, this study aimed to demonstrate the state of emerging trends and frontiers concerning the studies of stroke motor function rehabilitation during 2004-2022 through bibliometric software. Methods: Literature about stroke rehabilitation from 2004 to 2022 was retrieved from the Web of Science Core Collection. We used VOSviewer v.1.6.18.0, CiteSpace version 6.1.2, bibliometrix (R-Tool of R-Studio) and Scimago Graphica to analyze publication output, research categories, countries/institutions, authors/co-cited authors, journals/co-cited journals, co-cited references, and keywords. We plotted the co-citation map based on the analysis results to observe the research hotspots more intuitively. Results: A total of 3302 publications were retrieved, and the number of publication outputs per year increased over time. These articles were published from 78 different countries or regions and 564 institutions from 2004 to2022. In terms of national contribution, the United States produced the highest number of papers, followed by China, Japan, South Korea, and Canada. Amongall the institutions, Yeungnam Univ published the largest number of articles, followed by Emory Univ, Fudan Univ, Natl Taiwan Univ. Jang, Sung Ho and Wolf Sl are the most productive (56 published articles) and influential (cited 1121 times) authors respectively. Effect of constraint-induced movement therapy on upper extremity function 3 to 9 months after stroke - The EXCITE randomized clinical trial is the most frequently cited reference. Analysis of keywords showed that upper limbs, Fugl-Meyer assessment, electromyography, virtual reality, telerehabilitation, exoskeleton, and brain-computer interface have attracted great research interest currently, which may indicate the future research direction. Conclusion: Publications related to the rehabilitation of motor function after stroke are prone to increase continuously. The research on virtual reality, telemedicine, electroacupuncture, brain-computer interface as well as rehabilitation robots has attracted more and more attention, which has been the frontier and hot field of current research and developmental trends in the future research.